User behavior analysis on agriculture mining system - Sridevi, S; Bindu Prathyusha, M; V.S.J.Krishna Teja, P (International Journal of Engineering and Technology, 2018)
India being a horticulture nation yet utilizing conventional methods in agriculture. Right now suggestions for farmers depend upon the coordination among farmers and distinctive specialists. Proposed suggestions generally given to them by using past farming exercises with help of their knowledge and experience to give advanced outcomes. The proposed idea is the utilization of mining techniques in agriculture to give best suggestions to farmers for crops, crop rotation, prices of crops, quality of seeds and recognizable proofs of needed fertilizer. The system can be utilized by farmers as an application both on web and mobile. It is an advanced cultivating method that utilizesÂ  investigate information of soil qualities, soil types, crop yield information gathering and recommends the farmers to quality harvest in light of their site specific parameters. This diminishes the wrong decision on a harvest and increase in efficiency. With the progress of this rural modernization, agriculture site was progressively turning into a noteworthy instrument for farmers getting data about existence and generation. Step by step instructions to make the examination of the requirements of farmers viable to help them to discover the data assets of the Internet they were occupied with had turned into a dire and vital issue. It was vital hugeness in enhancing the structure and substance of agribusiness site, which could give better administrations to farmers and also enhance the level of modernization of horticultural generation.